2019
DOI: 10.1140/epjb/e2019-100240-3
|View full text |Cite
|
Sign up to set email alerts
|

Cascade overlap with vacancy-type defects in Fe

Abstract: In order to understand the effect of irradiation on the material properties, we need to look into the atomistic evolution of the system during the recoil event. The nanoscale features formed due to irradiation will ultimately affect the macroscopic properties of the material. The defect production in pristine materials have been subject to investigation previously, but as the dose increases, overlap will start to happen. This effect of cascades overlapping with pre-existing debris has only recently been touche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The multiple overlap cascade simulations by Granberg, Nordlund et al Refs. [24,81], carried out using the Fe potential by Mendelev, provide defect evolution data up to 0.16 NRT-DPA. Figure 13 plots the interstitial percentage versus cDPA arising from the early stages of Frenkel pair insertions along with scaled data originating from the cascade overlap simulations using the same empirical potential.…”
Section: Comparison To Cascade Overlap Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiple overlap cascade simulations by Granberg, Nordlund et al Refs. [24,81], carried out using the Fe potential by Mendelev, provide defect evolution data up to 0.16 NRT-DPA. Figure 13 plots the interstitial percentage versus cDPA arising from the early stages of Frenkel pair insertions along with scaled data originating from the cascade overlap simulations using the same empirical potential.…”
Section: Comparison To Cascade Overlap Simulationsmentioning
confidence: 99%
“…Simulations primarily explore the production of defects by impacts of energetic particle in the bulk of perfect crystals [17,18] or near surfaces [19,20]. Following the pioneering studies by Samaras et al [21,22], who analyzed how defects were produced by energetic collision events in nanocrystalline materials, extensive computer simulations have been performed exploring the effect of vacancy clusters [23,24], dislocations [25,26], dislocation loops [27], and grain boundaries [28] on defect production and accumulation in materials where the initial microstructure was different from the ideal periodic crystal lattice. Direct experimental observations show that the characteristic timescales of evolution of microstructure under irradiation depend strongly on the type of microstructure already present in the material.…”
Section: Introductionmentioning
confidence: 99%
“…This paper describes the interaction between cascades and pre-existing interstitial-type clusters. The effect of cascade overlap with vacancy-type defect clusters was not included in this study, as the effect was found to not be as considerable as for interstitial-type clusters [16]. The number of new Frenkel pairs (FPs) created in the close vicinity of a pre-existing cluster was presented by an analytical model [15].…”
Section: Methodsmentioning
confidence: 99%
“…change the Burgers vector of a dislocation loop [17]. In the same studies for iron, it was shown that the effect of interaction between cascades and pre-existing vacancy type clusters was not as significant [16].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation